Night of miracles : a novel - Berg, Elizabeth (Random House, 2018)
Lucille Howard is getting on in years, but she stays busy. Thanks to the inspiration of her dearly departed friend Arthur Truluv, she has begun to teach baking classes, sharing the secrets to her delicious buttercream yellow cake, the perfect pinwheel cookies, and other sweet essentials. Her classes have become so popular that she's hired Iris, a new resident of Mason, Missouri, as an assistant. Iris doesn't know how to bake but she needs to keep her mind off one big decision she sorely regrets. When a new family moves in next door and tragedy strikes, Lucille begins to look out for Lincoln, their son. Lincoln's parents aren't the only ones in town facing hard choices and uncertain futures. In these difficult times, the residents of Mason come together and find the true power of community--just when they need it the most.
Keywords: Domestic fiction